1995
DOI: 10.1128/jb.177.9.2497-2504.1995
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Neisseria gonorrhoeae PilA protein with the pilE promoter involves multiple sites on the DNA

Abstract: PilA is the putative DNA-binding component of a two-component system that regulates transcription of the pilin expression locus (pilE) of Neisseria gonorrhoeae. Here we report the purification of the PilA protein and characterization of its DNA-binding activity. PilA was overproduced in Escherichia coli with an isopropyl-␤-D-thiogalactopyranoside (IPTG)-inducible expression vector. Cell extracts were prepared by sonication and fractionated by anion-exchange chromotography, followed by dye affinity chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Whether or not this is truly unique to neisseriae remains to be seen. Our results also provide some insight into the previously puzzling observation that PilA binds to pilE promoter DNA in a sequence-specific manner (2). We now know that PilA, rather than functioning as a transcriptional regulator of gonococcal pilin biosynthesis, is part of the SRP protein targeting pathway (1).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Whether or not this is truly unique to neisseriae remains to be seen. Our results also provide some insight into the previously puzzling observation that PilA binds to pilE promoter DNA in a sequence-specific manner (2). We now know that PilA, rather than functioning as a transcriptional regulator of gonococcal pilin biosynthesis, is part of the SRP protein targeting pathway (1).…”
Section: Discussionmentioning
confidence: 71%
“…PilA exhibits anomalous sequence-specific DNA-binding activity (2). At the time the DNA-binding activity was identified, PilA was thought to be a transcriptional regulator that bound to promoter DNA to activate and/or repress transcription of the associated gene (54).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that PilA is a DNA-binding protein that binds specifically to a region 5Ј to the pilE1 promoter in a complex manner that may involve looping of the DNA (12). The PilA in these experiments was purified from a strain lacking pilB and was presumed to be unphosphorylated.…”
mentioning
confidence: 99%
“…1). The SRP54 proteins have two domains: an "M" domain, which interacts with the signal peptide of nascent proteins as well as to the 7 S (4.5 S in E. coli) RNA, and a "G" domain, which has the GTPase activity required for the interaction of the complex with the docking protein (19 Protein Purification-PilA was purified as described (12) with the following modification: Cibacron Blue 3GA-Agarose (Sigma) was used as the dye affinity resin, and PilA was batch-eluted from this resin at 0.3 M KCl. Protein concentration was determined using the Bradford method (Bio-Rad).…”
mentioning
confidence: 99%